The Influence of Product Quality and Price on Purchase Intention Alfamart Private Label Products - Devi Nopita Sari; Yunelly Asra (Politeknik Negeri Bengkalis, 2022)
This study aims to determine the effect of product quality and price on the purchase intention of Alfamart Private Label products in Bengkalis. This type of research is causal associative research using a quantitative approach. Associative causal research is research that aims to determine the effect between two or more variables. The type of data used is primary data and secondary data obtained from questionnaires and literature study. The population in this study was the entire Bengkalis community who had purchased private label Alfamart products. The sample in this study was 100 people. The sampling method used nonprobability sampling method with purposive sampling technique. The data analysis method used is associative statistical analysis, classical assumptions, correlation and regression analysis. With a determination coefficient of 0.705, so that product quality and price influence the purchase intention of Alfamart private label products by 70.5%, while the remaining 29.5% is not influenced by other factors examined in this study. The results showed that to determine the effect of product quality on the purchase intention of private label Alfamart products partially, the effect of price on purchase intentions of private label Alfamart products partially, the effect of product quality and price on purchase intentions of private label Alfamart Bengkalis products simultaneously